Triple metachronous primary pancreatic and gallbladder cancer associated with pancreaticobiliary maljunction: a case report - Yuta Kuhara; Yasushi Hashimoto; Satoshi Hirahara; Haruna Kubota; Kenji Shirakawa; Kazuhiro Toyota; Raita Yano; Hironori Kobayashi; Yujiro Yokoyama; Yoshihiro Sakashita; Yoshiaki Murakami; Kiyomi Taniyama; et al. (Surgical Case Reports, 2021)
Abstract Background Metachronous pancreatic and gallbladder cancer is a rare condition and has a dismal prognosis. Herein, we present a patient with triple metachronous primary pancreatic and gallbladder cancer associated with pancreaticobiliary maljunction who achieved long-term survival after undergoing repeat curative surgery. Case presentation A 65-year-old female patient with advanced gallbladder cancer associated with pancreaticobiliary maljunction underwent extended cholecystectomy with extrahepatic bile duct resection. The pathological diagnosis was T3N0M0 stage III A papillary adenocarcinoma with hepatic invasion. During a monthly follow-up, a diffuse hypovascular 2.0 × 1.5-cm mass was detected in the pancreatic head 6.2 years after the initial surgery. Hence, the patient underwent pancreaticoduodenectomy. Histological examination revealed T3N0M0 stage IIA well-differentiated adenocarcinoma without lymph node metastases. Marked inflammatory reaction was observed in the non-cancerous lesions of the proximal pancreatic head parenchyma containing bile pigment within ductular lumens. After 12.5 years from the initial surgery, total pancreatectomy for a 4.0 × 3.0-cm mass in the remnant pancreas was performed. Histological examination revealed T3N1M0 stage IIB moderately differentiated adenocarcinoma with lymph node metastases. Hence, surgical curative resection was achieved. Based on the pathological findings, a definitive diagnosis of triple metachronous pancreatic and gallbladder cancer was made. The pathology suggests no precursor lesions such as pancreatic intraepithelial neoplasia (PanIN) and atypical flat lesions, but marked inflammations in the non-cancerous lesions, strengthening our hypothesis that chronic inflammation induced by the pancreaticobiliary maljunction is related to carcinogenesis of the pancreas. Despite further adjuvant chemotherapy, the patient’s general condition worsened; however, she remained alive 15.2 years after the initial surgery while receiving the best supportive care. Conclusions Repeat curative surgery for triple metachronous cancer was associated with a favorable prognosis. Both the biliary tract and the pancreas should be closely monitored during follow-up among patients with pancreaticobiliary maljunction, which can be managed with curative surgery.